Genomic Insights of Multidrug-Resistant Escherichia coli From Wastewater Sources and Their Association With Clinical Pathogens in South Africa - Mbanga, Joshua; Amoako, Daniel G.; Abia, Akebe L. K.; Allam, Mushal; Ismail, Arshad; Essack, Sabiha Y. (Frontiers in Veterinary Science, 2021)
There is limited information on the comparative genomic diversity of antibiotic-resistant Escherichia coli from wastewater. We sought to characterize environmental E. coli isolates belonging to various pathotypes obtained from a wastewater treatment plant (WWTP) and its receiving waters using whole-genome sequencing (WGS) and an array of bioinformatics tools to elucidate the resistomes, virulomes, mobilomes, clonality, and phylogenies. Twelve multidrug-resistant (MDR) diarrheagenic E. coli isolates were obtained from the final effluent of a WWTP, and the receiving river upstream and downstream of the WWTP were sequenced on an Illumina MiSeq machine. The multilocus sequence typing (MLST) analysis revealed that multiple sequence types (STs), the most common of which was ST69 (n = 4) and ST10 (n = 2), followed by singletons belonging to ST372, ST101, ST569, ST218, and ST200. One isolate was assigned to a novel ST ST11351. A total of 66.7% isolates were positive for β-lactamase genes with 58.3% harboring the blaTEM1B gene and a single isolate the blaCTX−M−14 and blaCTX−M−55 extended-spectrum β-lactamase (ESBL) genes. One isolate was positive for the mcr-9 mobilized colistin resistance gene. Most antibiotic resistance genes (ARGs) were associated with mobile genetic support: class 1 integrons (In22, In54, In191, and In369), insertion sequences (ISs), and/or transposons (Tn402 or Tn21). A total of 31 virulence genes were identified across the study isolates, including those responsible for adhesion (lpfA, iha, and aggR), immunity (air, gad, and iss), and toxins (senB, vat, astA, and sat). The virulence genes were mostly associated with IS (IS1, IS3, IS91, IS66, IS630, and IS481) or prophages. Co-resistance to heavy metal/biocide, antibiotics were evident in several isolates. The phylogenomic analysis with South African E. coli isolates from different sources (animals, birds, and humans) revealed that isolates from this study mostly clustered with clinical isolates. Phylogenetics linked with metadata revealed that isolates did not cluster according to source but according to ST. The occurrence of pathogenic and MDR isolates in the WWTP effluent and the associated river is a public health concern.